MANAJEMEN PENDIDIKAN DALAM HADIST NABI (Tholabul Ilmi Faridhotun Ala Kulli Wuslimin Wal Muslimat) - Sodikin, Sodikin (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
In modern management science, the success of a leader cannot be separated from his intelligence in managing and managing all the potential of his members. The widespread spread of Islam was based on literacy and not the Prophet's success in encouraging the companions to learn. Whereas before the prophetic period, Arab society was known as an ummi society that was not good at reading and writing. If the success of the leader is determined by his managerial skills then of course the Prophet's success in the field of teaching contains elements of management that need to be studied so that it is known how he manages it. This paper seeks to examine the principles of the Prophet's educational management contained in various Hadith narrations by juxtaposing them with modern educational management principles. The spirit to move and do in the world of education can be categorized as the action and actualization of friends in the field of teaching. In the practice of teaching, the Prophet often asked his companions regarding what material he would convey to find out the extent of the companions' knowledge of the material.